Dinâmicas locais no município de Araguaína-TO: ICMS ecológico e suas possibilidades para a redução da vulnerabilidade socioambiental - Macedo, Jayrton Noleto de (Universidade Federal do Tocantins, 2021)
After several discussions after the widespread disclosure of the need to conserve the environment with eco 92, some nations began to mobilize incentives for the State itself to excel in environmental protection actions. The green ICMS / ecological ICMS public policy appears in Paraná, which is a way for the government to motivate itself, through financial incentives, in an attempt to promote environmental protection. The ecological ICMS is implemented in Tocantins in 2002 and since then it has been responsible for making the state transfer part of the accumulated ICMS tax to registered municipalities, requiring only that there be proof of environmental protection actions, for an annual period. The present work aims to evaluate how these evidences occurred in 2019, and how Araguaína carried out these environmental protection actions, more precisely in the area of environmental education. In addition, we tried to observe whether these actions are in line with the theoretical currents of environmental education. Methodologically the research took place in documents that Araguaína informed the organ responsible for the ecological ICMS, in the year. The research has the characteristic of documentary research, with the application of Sauvé's current theory (2005), instrumentalized from the materialistic dialectical method. At the end of the research, it was concluded that environmental education practices are poor in relation to the amount of money that Araguaína has received over the years, from this public policy, although this amount is not linked. The practices are within some streams of environmental education, and if they were applied in several public sectors and with greater scope, they could reduce the socio-environmental vulnerability in which the municipality is inserted, with greater effectiveness.